(untitled) - Marsh, Robert Mortimer (London, 1988)
This is a kind of book that you require currently. Besides, it can be your preferred book to check out after having this organizational change in japanese factories monographs in organizational behavior and Do you ask why? Well, organizational change in japanese factories monographs in organizational behavior and is a book that has various characteristic with others. You could not should know which the author is, how well-known the job is. As smart word, never ever judge the words from who speaks, yet make the words as your inexpensive to your life.
Keywords: Xã hội học công nghiệp,Industrial sociology; Nhật Bản,Japan